Comparison of the Effectiveness of Insulin Sensitizing Agents Metformin and Rosiglitazone in PCOS - Rıfat Emral; Uğur Ünlütürk; Gökhan Kabaçam; Ahmet Nuri Kamel (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Aim:Polycystic ovary syndrome (PCOS) is the most common endocrine disorder of child bearing-age women, and insulin resistance is one of the main characteristics of this syndrome. Although insulin sensitizing drugs are used to treat the clinical and biochemical features of PCOS, there is no certain data to offer using these agents in this syndrome. The aim of this study was to evaluate and compa-re the effectiveness of metformin versus rosiglitazone in the clinical and biochemical regression of PCOS.Methods: We enrolled 24 women with PCOS. Anthropometric measurements including body mass index (BMI) and waist circumference (waist) were obtained. All subjects underwent a hormonal as-sessment between 2nd and 6th day of menstrual cycle in which fasting plasma glucose (APG), insulin, LH, FSH, DHEAS, total and free testosterone levels measured after an overnight fasting. Homeostasis model assessment score (HOMA-IR) was calculated as a measure for insulin resistance. Hirsutism sco-res were assessed by using modified Ferriman Gallwey metod. All participants randomized either on metformin (1700 mg/day) or rosiglitazone (4mgr/day) treatment. After 24 weeks of application all pretreatment parameters assessed were reevaluated. Baseline and end-point measures were compa-red in the whole study cohort and also in the treatment groups separately.Results: There was a statistically significant correlation between basal insulin and free testostero-ne levels. When whole study cohorts are assessed after treatment with the insulin sensitizing drugs, free testosterone levels, hirsutism scores, and frequencies of menstrual cycles improved with signi-ficantly (p=.004, p=.049, and p=.001, respectively), while the improvement in fasting insulin levels and HOMA-IR measures did not reach statistical significance. When treatment groups were separately analyzed, similar results were achieved apart from the insignificant decrease in hirsutism scores wit-hin the metformin group.Conclusion: These findings suggest that both metformin and rosiglitazone improve clinical and bi-ochemical parameters of PCOS. It might be suggested that the effectiveness of these two drugs are not different from one another.